Gastropod Diversity in Pacar Pucang Laban Beach Tulungagung Regency - Rohmah, Tri Lestari Saidha; Afnani, Moh. Royhan; Rahayu, Dwi Anggorowati (Universitas Negeri Surabaya, 2025)
Tulungagung is a city that has a variety of beautiful beaches, one of which is Pacar beach. The condition of the beach which is still natural and clean makes this beach inhabited by a wide variety of marine biota, one of which is gastropods. The purpose of this study was to determine the diversity and relative abundance of Gastropods and the environmental conditions that affect Gastropods at Pacar Beach Pucang Laban, Tulungagung. Sampling used the transect method, by placing three transect lines. For each transect line was placed three square plots measuring 1x1 m2 each in each intertidal. Gastropods taken were gastropods that were found in each squared plot and in the substrate to a depth of 5 cm. The results of this study found 18 species belonging to 14 families. The results of the diversity obtained were based on the Shanon Wiener indeks are 2.461, which was dominated by the abundance of gastropods Clanculus atropurpureus and Conus (Lividoconus) lividus. The highest relative abundance came from the Trochidae family, Clanculus atropurpureus species of 20.97%, followed by the species Conus (Lividoconus) lividus from the Conidae family with a relative abundance of 17.74%.